Ginsenoside F1 promotes angiogenesis by activating the IGF-1/IGF1R pathway. (June 2019) - Zhang, Jiayan; Liu, Mingqun; Huang, Maohua; Chen, Minfeng; Zhang, Dong; Luo, Liangping; Ye, Geni; Deng, Lijuan; Peng, Yinghui; Wu, Xin; Liu, Guanping; Ye, Wencai; et al.
Graphical abstract: Abstract: Ischemic stroke is one of the most lethal and highly disabling diseases that seriously affects the human health and quality of life. A therapeutic angiogenic strategy has been proposed to alleviate ischemia-induced injury by promoting angiogenesis and improving cerebrovascular function in the ischemic regions. The insulin-like growth factor 1 (IGF-1)/insulin-like growth factor 1 receptor (IGF1R) axis is crucial for cerebral angiogenesis and neurogenesis. However, effective drugs that prevent cerebral ischemic injury by inducing cerebral angiogenesis via activation of the IGF1R pathway are lacking. Here, we screened a pro-angiogenic agent ginsenoside F1 (GF1), a ginseng saponin isolated from a traditional Chinese medicine that was widely used in ischemic stroke treatment. It promoted the proliferation, mobility and tube formation of human umbilical vein endothelial cells and human brain microvascular endothelial cells, as well as pericytes recruitment to the endothelial tubes. GF1 stimulated vessel sprouting in the rat arterial ring and facilitated neovascularization in chicken embryo chorioallantoic membrane (CAM). In the in vivo experiments, GF1 rescued the axitinib-induced vascular defect in zebrafish. It also increased the microvessel density (MVD) and improved focal cerebral blood perfusion in the rat middle cerebral artery occlusion (MCAO) model. Mechanism studies revealed that GF1-induced angiogenesis depended on IGF1R activation mediated by the autocrine IGF-1 loop in endothelial cells. Based on our findings, GF1-induced activation of the IGF-1/IGF1R pathway to promote angiogenesis is an effective approach to alleviate cerebral ischemia, and GF1 is a potential agent that improves cerebrovascular function and promotes recovery from ischemic stroke.